Cities of the world regional patterns and urban environments - Brunn, Stanley D. 1939-; Zeigler, Donald J. 1951-; Hays-Mitchell, Maureen 1956-; Graybill, Jessica K.
"Remarkably, more than half of the world's population now lives in cities, and the numbers grow daily as people abandon rural areas. This fully updated and revised seventh edition of the classic text offers readers a comprehensive set of tools for understanding the urban landscape, and, by extension, the world's politics, cultures, and economies. Providing a sweeping overview of world urban geography, noted experts explore the eleven major global regions. Each regional chapter considers urban history, economy, culture, and environment, as well as urban spatial models and problems and prospects. Each begins with two facing pages: a regional map that shows the major cities and a table of basic statistical information about cities and urbanization in each region and a list of ten salient points about that region's urban experience. Chapters conclude with a list of references, including films and webpages, which can be used by the student and instructor for additional information about specific cities. This edition adds the important new themes of climate change and migration, while continuing to focus specifically on sustainability, water, technology, social and environmental justice, security and conflict, the history of urban settlement, urban planning trends, and daily life. Vignettes of key cities give the reader a vivid understanding of daily life and the "spirit of place." The opening chapter presents an overview of key terms and concepts and explores contemporary world urbanization, and a concluding chapter projects the world's urban future. Liberally illustrated in full color with a new selection of photographs, maps, and diagrams, the text also includes a rich array of textboxes to highlight key topics ranging from migration and immigration to LBGTQ activism, human security, and climate change. Clearly written and timely, Cities of the World will be invaluable for those teaching introductory or advanced classes on global cities, regional geography, the developing world, and urban studies"-- Provided by publisher.